Binder composition for electrodes, cathode for lithium-sulfur battery and lithium-sulfur battery comprising the same
Patent Information
- Application Number
- KR1020220183527
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-12-23
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2042-12-23
Abstract
Description
Technology Field
[0001] The present invention relates to a binder composition for an electrode, a positive electrode for a lithium-sulfur battery comprising the same, and a lithium-sulfur battery. Background Technology
[0003] As the application range of lithium-ion batteries expands beyond portable electronic devices to include electric vehicles (EVs) and energy storage systems (ESS), the demand for high-capacity, high-energy-density, and long-life lithium-ion batteries is increasing.
[0004] Among various types of lithium-ion batteries, the lithium-sulfur battery is a battery system that uses a sulfur compound containing a sulfur-sulfur (SS) bond as the positive electrode active material and lithium metal as the negative electrode active material. Lithium-sulfur batteries have the advantages of being easy to procure, inexpensive, non-toxic, and environmentally friendly, as sulfur, the main component of the positive electrode, has a low atomic weight and is very abundant. Furthermore, lithium-sulfur batteries are attracting attention among rechargeable batteries developed to date because they exhibit high capacity compared to other battery systems.
[0005] The sulfur used in lithium-sulfur batteries has an electrical conductivity of approximately 5 x 10⁻⁶ -30 Since it is an insulator with no electrical conductivity (S / cm), the movement of electrons generated by electrochemical reactions is difficult; therefore, sulfur-containing materials are combined with conductive materials such as carbon, which can provide electrochemical reaction sites, into sulfur-carbon composites and used as positive electrode active materials.
[0006] Meanwhile, in a lithium-sulfur battery, during discharge, lithium, the negative electrode active material, releases electrons and ionizes into lithium cations, undergoing oxidation, while the sulfur-based material, the positive electrode active material, accepts electrons and undergoes reduction. Here, through the reduction reaction of the sulfur-based material, the aforementioned SS bond accepts two electrons and is converted into a sulfur anion. The lithium cations generated by the oxidation reaction of lithium are transferred to the positive electrode through the electrolyte, where they combine with the sulfur anions produced by the reduction reaction of the sulfur-based compound to form a salt. Specifically, sulfur prior to discharge has a cyclic S8 structure, which, through a reduction reaction, becomes lithium polysulfide (Li2S2). x It is converted to , x = 8, 6, 4, 2), and completely reduced to lithium sulfide (Li2 S ) is generated. However, lithium polysulfide generated during the charging and discharging process easily leaches into the electrolyte, causing a decrease in battery capacity and cell degradation. To solve this problem of lithium polysulfide leaching, sulfur is loaded into the pores of various porous carbon materials and utilized in the cathode.
[0007] However, since sulfur-carbon composites containing porous carbon materials have low density and a large surface area, a binder with high adhesion is required for use in anodes. Accordingly, although research has been conducted on various binders, it has been difficult to simultaneously improve productivity, output performance, and adhesion. The problem to be solved
[0009] The present invention was devised to solve the problems of the prior art as described above, and aims to provide an electrode binder composition, a positive electrode for a lithium-sulfur battery, and a lithium-sulfur battery that can improve adhesion at the electrode while maintaining high levels of productivity and output performance.
[0010] It will be readily apparent that other objects and advantages of the present invention can be realized by means or methods described in the claims and combinations thereof. means of solving the problem
[0012] The inventors have discovered that the above problem can be solved through the following electrode binder composition, a positive electrode for a lithium-sulfur battery containing the same, and a lithium-sulfur battery.
[0013] According to the first embodiment,
[0014] It includes a first binder resin, a second binder resin, and a third binder resin, and
[0015] The first binder resin above is lithium-substituted polyacrylic acid, and
[0016] The above second binder resin is polyvinyl alcohol, and
[0017] The above third binder resin is a colloidal particle type water-based binder resin,
[0018] This relates to a binder composition for electrodes.
[0019] According to the second embodiment, in the first embodiment
[0020] The present invention relates to a binder composition for a secondary battery electrode, wherein the first binder resin comprises at least one lithium-substituted polyacrylic acid, and the weight-average molecular weight (MW) of the lithium-substituted polyacrylic acid is 300,000 to 1,500,000.
[0021] According to the third embodiment, in the first embodiment or the second embodiment,
[0022] The above first binder resin relates to a binder composition for a secondary battery electrode comprising at least two types of lithium-substituted polyacrylic acids having different molecular weights.
[0023] According to the fourth embodiment, in any one of the first to third embodiments,
[0024] The present invention relates to an electrode binder composition having a weight-average molecular weight (MW) of the second binder resin of the above-mentioned second binder resin of 10,000 to 1,000,000.
[0025] According to the fifth embodiment, in any one of the first to fourth embodiments,
[0026] The third binder resin relates to a binder composition for electrodes, wherein the binder resin is a colloidal particle comprising styrene butadiene rubber, an acrylic polymer containing repeating units derived from at least one monomer among acrylic monomers, or a mixture of two or more of these.
[0027] According to the 6th embodiment, in any one of the 1st to 5th embodiments,
[0028] The present invention relates to an electrode binder composition further comprising a water-based binder resin as a fourth binder resin.
[0029] According to the seventh embodiment, in any one of the first to sixth embodiments,
[0030] Based on a total of 100% by weight of the above electrode binder composition,
[0031] The above first binder resin is 10 to 80 weight%,
[0032] The above second binder resin is 1 to 50 weight%, and
[0033] The above third binder resin relates to a binder composition for electrodes comprising 10 to 80 weight%.
[0034] According to the eighth embodiment, in any one of the first to seventh embodiments,
[0035] Based on a total of 100% by weight of the above electrode binder composition,
[0036] The above first binder resin is 25 to 50 weight%,
[0037] The above second binder resin is 10 to 25 weight%, and
[0038] The above-mentioned third binder resin relates to a binder composition for electrodes comprising 35 to 50 weight%.
[0039] According to the ninth embodiment,
[0040] It includes a positive current collector and a positive active material layer formed on at least one surface of the positive current collector, and
[0041] The above positive active material layer comprises a positive active material and a binder resin, and
[0042] The above binder resin relates to a positive electrode for a lithium-sulfur battery comprising an electrode binder composition described in any one of the first to eighth embodiments.
[0043] In the 10th embodiment,
[0044] The present invention relates to a lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte according to a ninth embodiment. Effects of the invention
[0045] The present invention provides an electrode binder composition having a novel composition, comprising lithium-substituted polyacrylic acid, polyvinyl alcohol, and a colloidal particulate water-based binder resin. By doing so, it is possible to maintain high levels of productivity and output performance while exhibiting excellent adhesion. Specific details for implementing the invention
[0047] The present invention will be described in detail below. Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical spirit of the present invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention. Accordingly, the embodiments described in this specification and the configurations illustrated in the drawings are merely one preferred embodiment of the present invention and do not represent all of the technical spirit of the present invention; therefore, it should be understood that various equivalents and modifications capable of replacing them may exist at the time of filing this application.
[0049] Throughout this specification, when a part is described as "include(s) or comprise(s)" a component, unless specifically stated otherwise, this means that it does not exclude other components but may include additional components.
[0051] Additionally, terms such as “about,” “substantially,” as used throughout this specification, are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding this invention.
[0053] Throughout this specification, the description “A and / or B” means “A or B or both.”
[0055] Throughout the entire specification, unless otherwise specified, temperature refers to Celsius temperature, and the unit is °C.
[0057] The present invention relates to a composition for an electrode binder, a positive electrode for a lithium-sulfur battery comprising the same, and a lithium-sulfur battery.
[0059] Binder composition for electrodes
[0060] In one embodiment of the present invention, the electrode binder composition comprises a first binder resin, a second binder resin, and a third binder resin, wherein the first binder resin is lithium-substituted polyacrylic acid, the second binder resin is polyvinyl alcohol, and the third binder resin is a colloidal particle-type water-based binder resin. By including a specific combination of the first binder resin and the second binder resin, which contribute to improving processability, and the third binder resin, which contributes to improving adhesion, the present invention can provide an electrode binder composition capable of maintaining high levels of productivity and output performance while exhibiting excellent adhesion. Furthermore, optimal battery output and high adhesion can be simultaneously secured depending on the mixing ratio of the second binder resin, which has interfacial properties that enable efficient adhesion of the first binder resin and the third binder resin, which are advantageous for output. The electrode binder composition according to the present invention can be applied to both a cathode and / or an anode, and in particular, the type of electrode is not limited as long as an aqueous solvent can be applied during the manufacture of the electrode.
[0062] The first binder resin is lithium-substituted polyacrylic acid.
[0063] The lithium-substituted polyacrylic acid described above is a form in which the hydrogen of a carboxyl group (COOH) in polyacrylic acid is substituted with lithium. The lithium-substituted polyacrylic acid can be formed through a neutralization reaction by adding a base containing lithium to the polyacrylic acid. It may be preferable for the lithium-substituted polyacrylic acid to be formed by completely neutralizing the polyacrylic acid by adding a base such that the ratio of the carboxyl group of the polyacrylic acid to the amount of lithium is 1:1 molar. For example, the lithium-substituted polyacrylic acid of the present invention may be formed by neutralizing it using LiOH so that the pH is in the range of 6 to 9. If the polyacrylic acid is not completely neutralized, side reactions may occur due to hydrogen generated from the polyacrylic acid. In addition, if an excessive amount of base is added, the lifespan characteristics of the battery may deteriorate due to the base that does not participate in the neutralization reaction. Through the aforementioned lithium substitution, the polarity of the polyacrylic acid increases, and its dispersibility in a solvent may be improved. The above lithium-substituted polyacrylic acid not only serves as a binder to increase adhesion between electrode active materials and / or between electrode active materials and electrode current collectors, but can also improve electrode stability by suppressing by-products generated during battery operation.
[0064] According to one embodiment of the present invention, the first binder resin comprises at least one lithium-substituted polyacrylic acid, and the lithium-substituted polyacrylic acid may have a weight-average molecular weight (MW) of 300,000 to 1,500,000. By including a lithium-substituted polyacrylic acid having a weight-average molecular weight within the above range, electrode adhesion and productivity can be improved.
[0065] When at least two types of the lithium-substituted polyacrylic acid are included, the molecular weight of each lithium-substituted polyacrylic acid is different. Specifically, the lithium-substituted polyacrylic acid may include at least one type, at least two types, or at least three types.
[0066] When at least two types of the above lithium-substituted polyacrylic acid are included, the lithium-substituted polyacrylic acid with a relatively high molecular weight can contribute to increasing the adhesion of the binder and improving the lifespan stability of the battery, while the lithium-substituted polyacrylic acid with a relatively low molecular weight can increase the content of solids during slurry preparation and increase the flowability of the slurry, thereby contributing to improving the processability of the binder. Accordingly, the at least two types of lithium-substituted polyacrylic acids of the present invention may be configured to include one type of lithium-substituted polyacrylic acid with a relatively high molecular weight and one type of lithium-substituted polyacrylic acid with a relatively low molecular weight.
[0067] In this specification, the weight average molecular weight (Mw) may be determined as a converted value for standard polystyrene measured by gel permeation chromatography (GPC), and specifically, may be determined by gel permeation chromatography (GPC) as described in ASTM method D5296. For example, the following GPC measurement conditions may be presented.
[0068] GPC measuring device: ACQUITY APC (Waters)
[0069] Column: PL gel Mixed-B + C (Agilent)
[0070] Column temperature: RT (20~25℃)
[0071] Eluent: DMF / 0.05M LiBr
[0072] Flow rate: 1.0 ml / min
[0073] Detector: Waters 2414 RI detector
[0074] Sample concentration: ~1 mg / ml (0.45 µm syringe filter)
[0075] Injection volume: 10 µl
[0076] Correction curve: Polystyrene.
[0078] The second binder resin mentioned above is polyvinyl alcohol.
[0079] The above-mentioned polyvinyl alcohol can provide excellent adhesion to the surface of the electrode active material as well as the electrode current collector due to the hydroxyl groups repeatedly formed in the main chain of the polymer. In addition, the above-mentioned polyvinyl alcohol can act as a dispersant within the binder composition. In particular, when mixed with the positive electrode active material, it can improve the dispersibility of the positive electrode active material.
[0080] The weight-average molecular weight (MW) of the above polyvinyl alcohol may be 10,000 to 1,000,000. By including polyvinyl alcohol having a weight-average molecular weight within the above range, the desired adhesive strength and dispersibility can be secured.
[0081] The viscosity of the second binder resin may be 100 to 10,000 cp, or 1,000 to 10,000 cp. Specifically, the viscosity of a 5 to 10% aqueous solution or a 7% aqueous solution of the second binder resin may have a viscosity within the above range. By including polyvinyl alcohol having a viscosity within the above range, the desired adhesive strength and dispersibility can be secured. If a second binder resin with a low viscosity within the above range is used, better dispersibility can be secured, and if a second binder resin with a high viscosity within the above range is used, better adhesive strength can be obtained.
[0082] In this specification, the term "viscosity" refers to a value measured at a predetermined temperature (25°C) using a viscometer commonly used to measure the viscosity of a fluid, such as a Type B viscometer (VISCOMETER, TOKIMEC) or a rheometer (Rheometer, TA instruments). For example, in this specification, viscosity can preferably be measured at 25°C at a shear rate of 12 rpm using a Type B viscometer.
[0084] The above third binder resin is a colloidal particle type water-based binder resin.
[0085] The above-mentioned colloidal particle type water-based binder resin can suppress the increase in viscosity of the dissolved polymer and the binder composition by existing in an undissolved particle state within the water-based binder composition, and can serve as a binder that increases adhesion between electrode active materials and / or between electrode active materials and electrode current collectors.
[0086] The above colloidal particle-type water-based binder resin exists in a state dispersed in a water-based solvent and is stably dispersed in a particle state that is not dissolved, has a shape close to spherical, and has an average particle size (D50) of 10 nm to 1 μm or 50 to 500 nm. The above average particle size (D50) may refer to the particle size at the 50% point of the cumulative distribution of the number of particles according to particle size.
[0087] The above colloidal particle type water-based binder resin may be styrene butadiene rubber, an acrylic polymer comprising repeating units derived from at least one monomer among acrylic monomers, or a mixture of two or more of these.
[0088] The above acrylic polymer may be applied without limitation as long as it includes repeating units derived from at least one acrylic monomer, for example, it may be an acrylic polymer derived from one acrylic monomer or a copolymer containing repeating units derived from at least two acrylic monomers.
[0089] The above acrylic monomer may be acrylic acid, alkyl acrylate, alkyl methacrylate, isoalkyl (meth)acrylate, etc., wherein "alkyl" may be an alkyl group having 1 to 10 carbon atoms, and more specifically, may be an alkyl group having 1 to 5 carbon atoms. Specific examples may include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, etc. Preferably, the above acrylic monomer may include an acrylic copolymer comprising repeating units derived from acrylic acid and butyl (meth)acrylate.
[0091] In a specific embodiment of the present invention, in the electrode binder composition, the content of the first binder resin, the second binder resin, and the third binder resin may be included within the range to be described below.
[0092] Specifically, the first binder resin may be included in an amount of 10 to 80 weight%, specifically 10 to 50 weight%, or 25 to 50 weight%, based on 100 weight% of the total binder composition for the electrode. By including the content of the first binder resin within the range described above, the sedimentation phenomenon of the positive electrode active material can be suppressed.
[0093] The second binder resin may be included in an amount of 1 to 50 weight%, specifically 1 to 25 weight%, or 10 to 25 weight%, based on 100 weight% of the total electrode binder composition. By including the content of the second binder resin within the range described above, excellent adhesion between positive active materials and / or between positive active materials and positive current collectors can be provided.
[0094] The third binder resin may be included in an amount of 10 to 80 weight%, specifically 10 to 50 weight% or 35 to 50 weight%, based on 100 weight% of the total electrode binder composition. By including the content of the third binder resin within the range described above, excellent adhesion between positive active materials and / or between positive active materials and positive current collectors can be provided.
[0095] Since the first binder resin, the second binder resin, and the third binder resin all satisfy the suggested content range, not only is improved adhesion at the electrode exhibited, but improved battery performance can also be exhibited, and since a positive electrode with an appropriate weight that is not excessive can be manufactured, balanced cell energy density can be provided, which is advantageous in terms of battery capacity.
[0097] According to a specific embodiment of the present invention, the electrode binder composition of the present invention may further include a water-based binder resin as a fourth binder resin.
[0098] The above-mentioned fourth binder resin is different from the above-mentioned first to third binder resins and may include, for example, carboxymethyl cellulose (CMC), hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, polyethylene glycol, polyacrylonitrile, polyacrylamide, or a mixture of two or more of these.
[0100] <Cathode for Lithium-Sulfur Batteries>
[0101] In one embodiment of the present invention, the positive electrode for a lithium-sulfur battery is,
[0102] It includes a positive current collector and a positive active material layer formed on at least one surface of the positive current collector, and
[0103] The above positive active material layer includes a positive active material and a binder resin.
[0104] The above positive active material may comprise 50 to 99 weight% or 90 to 99 weight% with respect to 100 weight% of the positive active material layer. Additionally, the binder resin may comprise 0.5 to 10 weight% or 1 to 5 weight% with respect to 100 weight% of the positive active material layer.
[0106] The above-mentioned positive current collector is intended to support the positive active material and is not particularly limited as long as it possesses high conductivity without causing chemical changes in the battery. The above-mentioned positive current collector can generally be made with a thickness of 3 to 500 μm, and conductive materials such as stainless steel, aluminum, copper, and titanium can be used. When a carbon-coated aluminum substrate is used, it has the advantages of excellent adhesion to the positive active material, low contact resistance, and prevention of corrosion caused by polysulfides of aluminum. In addition, the above-mentioned positive current collector can take various forms, such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0108] The above-mentioned positive active material may include at least one selected from the group consisting of sulfur-based materials, specifically elemental sulfur (S8) and sulfur compounds. The above-mentioned sulfur-based materials include inorganic sulfur (S8) and Li2S n (n≥1), disulfide compounds such as 2,5-dimercapto-1,3,4-thiadiazole, 1,3,5-trithiocyanuic acid, organic sulfur compounds, and carbon-sulfur polymers ((C2S x ) n It may be one or more selected from the group consisting of x=2.5 to 50, n≥2). Preferably, the positive active material may include inorganic sulfur (S8).
[0109] Since the sulfur contained in the above-mentioned positive electrode active material does not possess electrical conductivity on its own, it is used together with a conductive material such as a carbon material. Therefore, the above-mentioned positive electrode active material may be a sulfur-carbon composite, and the above-mentioned sulfur-carbon composite may include a sulfur-based material.
[0110] The carbon included in the above sulfur-carbon composite is a porous carbon material that provides a framework capable of uniformly and stably fixing sulfur and compensates for the low electrical conductivity of sulfur, thereby enabling the electrochemical reaction to proceed smoothly.
[0111] The porous carbon material can generally be manufactured by carbonizing various carbonaceous precursors. The porous carbon material may contain non-uniform pores internally, the average diameter of the pores may be in the range of 1 to 200 nm, and the porosity may be in the range of 10 to 90% of the total volume of the porous carbon material. If the average diameter of the pores is smaller than the above range, the pore size is only at the molecular level, making sulfur impregnation impossible. Conversely, if the average diameter of the pores exceeds the above range, the mechanical strength of the porous carbon material is weakened, making it undesirable for application in the electrode manufacturing process.
[0112] The shape of the above porous carbon material is spherical, rod, needle, plate, tube, or bulk, and can be used without limitation as long as it is commonly used in lithium-sulfur batteries.
[0113] The porous carbon material may have a porous structure or a high specific surface area, and may be one commonly used in the industry. For example, the porous carbon material may include graphite; graphene; carbon black such as Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black; carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT); carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), and activated carbon fibers (ACF); graphite such as natural graphite, artificial graphite, and expanded graphite; activated carbon, etc. Preferably, the porous carbon material may be a carbon nanotube.
[0114] The above sulfur-carbon composite may contain a sulfur-based material in an amount of 60 to 90 wt%, preferably 65 to 85 wt%, and more preferably 70 to 80 wt% relative to 100 wt% of the sulfur-carbon composite. If the content of the sulfur-based material is lower than the above range, the content of the porous carbon material within the sulfur-carbon composite increases relatively, thereby increasing its specific surface area and consequently increasing the amount of binder used relative to the sulfur content during the manufacture of the anode. This increase in the amount of binder used ultimately increases the sheet resistance of the anode and acts as an insulator that blocks the passage of electrons, thereby degrading the performance of the battery. Conversely, if the content of the sulfur-based material exceeds the above range, sulfur that cannot bond with the porous carbon material aggregates or re-leaches to the surface of the porous carbon material, making it difficult to accept electrons and participate in electrochemical reactions, resulting in a decrease in battery capacity.
[0115] In addition, in the sulfur-carbon composite, sulfur is located on at least one of the inner and outer surfaces of the aforementioned porous carbon material, wherein sulfur may be present in an area of less than 100%, preferably 1 to 95%, and more preferably 60 to 90% of the total inner and outer surfaces of the porous carbon material. When sulfur is present on the inner and outer surfaces of the porous carbon material within the above range, it can exhibit maximum effects in terms of electron transfer area and wettability with the electrolyte. Specifically, since sulfur is thinly and uniformly impregnated on the inner and outer surfaces of the porous carbon material within the above range, the electron transfer contact area can be increased during the charge-discharge process. If sulfur is located on 100% of the total area of the inner and outer surfaces of the porous carbon material, the carbon material is completely covered with sulfur, resulting in poor wettability with the electrolyte and poor contact with the included electrically conductive material, so it cannot receive electrons from the electrode and cannot participate in the electrochemical reaction.
[0116] The method for manufacturing the above sulfur-carbon composite is not particularly limited in the present invention, and methods commonly used in the art may be used. For example, a method of simply mixing sulfur and a porous carbon material and then heat-treating them to form a composite may be used.
[0117] In addition to the above, the positive electrode active material may further include transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, alloys of these elements and sulfur, and one or more additives selected from the aforementioned components.
[0118] The above transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., and group IIIA elements may include Al, Ga, In, Tl, etc., and group IVA elements may include Ge, Sn, Pb, etc.
[0119] The sulfur may be included in an amount of 40 to 95 weight%, preferably 50 to 90 weight%, and more preferably 60 to 85 weight%, relative to 100 weight% of the positive active material layer constituting the positive electrode. In one embodiment of the present invention, when a sulfur-carbon composite is used as the positive active material, the sulfur-carbon composite may be included in an amount of 90 weight% to 97 weight% relative to 100 weight% of the positive active material layer. If the content of the positive active material is less than the above range, it is difficult to sufficiently exhibit the electrochemical reaction of the positive electrode. Conversely, if the content exceeds the above range, the content of the conductive material and binder described below is relatively insufficient, causing the resistance of the positive electrode to increase and the physical properties of the positive electrode to deteriorate.
[0121] The above binder resin includes the electrode binder composition described above. Specifically, the above binder resin may be the electrode binder composition described above.
[0123] The above-described positive electrode for a lithium-sulfur battery can be manufactured by applying a positive electrode slurry comprising the above-described positive electrode active material and the above-described binder resin onto a positive electrode current collector.
[0124] In one embodiment of the present invention, the anode slurry may have a solid content concentration of 20 wt% to 50 wt%. In the present invention, solid content refers to solid components in the slurry excluding solvents, etc.
[0125] The above anode slurry may additionally include additives, which are materials commonly used to improve its function, as needed, and since the specific types of additives can be ordinary ones, a description is omitted in this specification.
[0126] In the present invention, the method of applying the anode slurry is not particularly limited, and methods such as the doctor blade method, die casting method, comma coating method, and screen printing method may be used. In addition, after forming on a separate substrate, the anode slurry can be applied onto the anode current collector by a press or lamination method.
[0127] After the above coating, a drying process may be performed to remove the solvent. The drying process is performed at a temperature and time sufficient to remove the solvent, and since the conditions may vary depending on the type of solvent, they are not specifically limited in the present invention. Examples of drying methods may include drying methods using warm air, hot air, or low-humidity air, vacuum drying methods, and drying methods using (far-infrared) radiation or electron beam irradiation. The drying speed can generally be adjusted so that the solvent is removed as quickly as possible within a speed range where cracks do not occur in the positive active material layer due to stress concentration and the positive active material layer does not peel off from the positive current collector.
[0128] In addition, the density of the positive active material within the positive electrode can be increased by applying pressure to the current collector after the above drying. Examples of pressing methods include mold pressing and roll pressing.
[0130] lithium-sulfur battery
[0131] In one embodiment of the present invention, a lithium-sulfur battery is provided comprising a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode comprises the positive electrode described above.
[0133] The above-mentioned negative electrode may be used without limitation as long as it is conventionally usable as a negative electrode of a lithium-sulfur battery. Specifically, the above-mentioned negative electrode may be a lithium-based metal, and may further include a current collector on one side of the lithium-based metal. The above-mentioned current collector may be a negative electrode current collector.
[0134] The above lithium-based metal may be lithium or a lithium alloy. In this case, the lithium alloy includes an element capable of alloying with lithium, and specifically, it may be an alloy of lithium with one or more elements selected from the group consisting of Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.
[0135] The above lithium-based metal may be in the form of a sheet or foil, and in some cases, may be in the form in which lithium or a lithium alloy is deposited or coated on a current collector by a dry process, or in the form in which a particulate metal and alloy are deposited or coated by a wet process, etc.
[0136] The above-mentioned negative electrode current collector is not particularly limited as long as it possesses high conductivity without causing chemical changes in the battery, and may be selected from the group consisting of copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, or silver, and the alloy may be an aluminum-cadmium alloy; additionally, calcined carbon, non-conductive polymers or conductive polymers surface-treated with a conductive material may be used. Generally, a copper foil is applied as the negative electrode current collector. Furthermore, various forms may be used, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics with or without fine irregularities formed on the surface. Additionally, the above-mentioned negative electrode current collector is applied with a thickness range of 3 to 50 μm. If the thickness of the above-mentioned cathode current collector is less than 3 μm, the current collection effect is reduced, whereas if the thickness exceeds 50 μm, there is a problem that processability is reduced when assembling the cell by folding.
[0138] In one embodiment of the present invention, the electrolyte may be used without limitation as long as it is one that can be conventionally used as an electrolyte for a lithium-sulfur battery. Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0139] The above organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. The above organic solvent may be any that is commonly used in lithium secondary battery electrolytes without limitation, and for example, ethers, esters, amides, chain carbonates, cyclic carbonates, etc., may be used alone or in combination of two or more. Among these, ether-based compounds may be included as a representative example.
[0140] The above ether-based compounds may include acyclic ethers and cyclic ethers. For example, the above-mentioned acyclic ether may be one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether. For example, the cyclic ether is 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, It may be one or more selected from the group consisting of 1,3-dimethoxybenzene, 1,4-dimethoxybenzene and isosorbid dimethyl ether, furan, 2-methyl furan, 3-methyl furan, 2-ethyl furan, 2-butyl furan, 2,3-dimethyl furan, 2,4-dimethyl furan, 2,5-dimethyl furan, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzoburane, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene, but is not limited thereto.
[0141] Examples of the esters of the above organic solvents include, but are not limited to, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone and mixtures of two or more of these.
[0142] Specific examples of the above linear carbonate compounds include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethylmethyl carbonate (EMC), methylpropyl carbonate and ethylpropyl carbonate, or a mixture of two or more of these.
[0143] In addition, specific examples of the above-mentioned cyclic carbonate compounds may include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and their halides, or mixtures of two or more of these. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).
[0144] The above lithium salt is a compound capable of providing lithium ions in the electrolyte. Examples of such lithium salts include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3CO2, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiCH3SO3, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiC4BO8, LiCl, LiBr, LiB 10 Cl 10Li, LiI, or LiB(C2O4)2, etc., may be used. In the present invention, in order to increase the potential for sulfur utilization and to realize high-capacity and high-voltage batteries, it is preferable to include Li-TFSI as the lithium salt. More preferably, the lithium salt may include LiN(CF3SO2)2(Li-TFSI) at a content of 80 wt% or more, 90 wt% or more, or 100% relative to 100 wt% of the total lithium salt.
[0145] The concentration of the lithium salt is in the range of 0.1 to 2.0 M, preferably 0.5 to 1 M, and more preferably 0.5 to 0.75 M. When the concentration of the lithium salt falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and allow lithium ions to move effectively. If the concentration of the lithium salt is below the above range, it may be difficult to secure ion conductivity suitable for battery operation, and if it exceeds the above range, the viscosity of the electrolyte increases, which may reduce the mobility of lithium ions, or the decomposition reaction of the lithium salt itself increases, which may degrade the performance of the battery.
[0146] In addition to the electrolyte components, the above electrolyte may further include additives for the purpose of improving the lifespan characteristics of the battery, suppressing the reduction of battery capacity, and improving the discharge capacity of the battery. For example, the above additives may include nitrate compounds, nitrite compounds, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ethers, ethylene diamine, n-glyme, hexamethylphosphate triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, either alone or in combination. The above additives may be included in an amount of 0.1 to 10 wt%, preferably 0.1 to 5 wt%, based on the total weight of the electrolyte.
[0147] In a specific embodiment of the present invention, the electrolyte may include a nitric acid compound and / or a nitrite-based compound as an additive. Such nitric acid compound / nitrite-based compound forms a stable film on the lithium metal electrode serving as the negative electrode and has the effect of improving charge and discharge efficiency. Such nitric acid or nitrite-based compounds include inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), and ammonium nitrite (NH4NO2); Organic nitric acid or nitrite compounds such as methyl nitrate, dialkyl imidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, pentyl nitrite, octyl nitrite, etc.; organic nitro compounds such as nitromethane, nitroprophane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene, etc., and combinations thereof may include one or more selected from the group consisting of these, but are not limited thereto. In a preferred embodiment of the present invention, the additive may include lithium nitrate.
[0149] In one embodiment of the present invention, the separator is disposed within an electrode assembly in a manner interposed between a negative electrode and an anode. The separator separates the negative electrode and the anode and provides a pathway for the movement of lithium ions; it may be used without limitation as long as it is conventionally usable as a separator for a lithium-sulfur battery. Specifically, the separator may include a porous polyolefin substrate, and, if necessary, may further include inorganic particles and / or a binder for binding said inorganic particles on at least one surface of said porous polyolefin substrate.
[0150] In addition, the separator may be a film-shaped electrolyte membrane containing a solid electrolyte, and may further include a binder for binding the solid electrolyte as needed. The solid electrolyte may be used without limitation as long as it is a polymer-based solid electrolyte, an inorganic-based solid electrolyte, or a mixture thereof, provided it is commonly used in lithium-sulfur batteries.
[0152] In one embodiment of the present invention, the external shape of the lithium-sulfur battery may be, for example, coin-shaped, cylindrical, pouch-shaped, or prismatic, and the external shape of the battery is not particularly limited. Furthermore, the lithium-sulfur battery may be used not only as a battery cell used as a power source for small devices but also as a unit cell in a medium-to-large battery module comprising a plurality of battery cells, and the form of use is not particularly limited.
[0154] In one embodiment of the present invention, a lithium-sulfur battery using a cathode comprising the sulfur-carbon composite described above may exhibit excellent effects in terms of the energy density of the battery, but the effects of the present invention are not limited thereto. Furthermore, the lithium-sulfur battery may exhibit an effect of significantly improving energy density by increasing the loading amount of sulfur in the electrode and reducing the amount of electrolyte, but the effects of the present invention are not limited thereto.
[0156] Hereinafter, the present invention will be described in detail with reference to examples in order to specifically explain the invention. However, the embodiments according to the present invention may be modified in various different forms, and the scope of the present invention should not be interpreted as being limited to the embodiments described above. The embodiments of the present invention are provided to more completely explain the invention to those with average knowledge in the art.
[0158] <Example>
[0159] Example 1
[0160] 1) Anode fabrication
[0161] A first polyacrylic acid (Sigma-Aldrich, weight-average molecular weight 450,000) and a second polyacrylic acid (Sigma-Aldrich, weight-average molecular weight 1,250,000) were mixed and then completely neutralized with lithium hydroxide to produce a lithium-substituted polyacrylic acid.
[0162] A binder composition was prepared by mixing the above lithium-substituted polyacrylic acid with polyvinyl alcohol (Sigma-Aldrich) and acrylic colloid (acrylic acid ester copolymer, GL Chem). Their weight ratios and weight-average molecular weights are as shown in Table 1.
[0163] In addition, a positive electrode active material, which is a sulfur-carbon composite, was prepared by mixing sulfur (Sigma-Aldrich) with CNT (Carbon Nanotube) using a ball mill at a mixing ratio of 70:30 and then heat-treating at 155°C.
[0164] The aforementioned binder composition and cathode active material were added to water, a solvent, in a ratio of 4:96 and mixed to prepare a cathode slurry; the prepared cathode slurry was then applied to an aluminum foil current collector and dried at 50°C for 2 hours to obtain a loading amount of 3 mAh / cm² 2 The anode of was manufactured.
[0166] 2) Manufacturing of lithium-sulfur batteries
[0167] A lithium foil with a thickness of about 40 μm was used as the cathode.
[0168] A polyethylene porous membrane (thickness of about 9 μm, porosity of about 40% to 45%) was used as a separator.
[0169] As an electrolyte, a mixture of 1 M concentration lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt% lithium nitrate (LiNO3) dissolved in an organic solvent composed of dioxolane (DOL) and dimethyl ether (DME) in a 1:1 (volume ratio) was used.
[0171] A lithium-sulfur battery was manufactured by positioning the above-manufactured positive and negative electrodes facing each other, placing the above-manufactured separator between them, and then injecting the above-manufactured electrolyte.
[0173] Examples 2 to 8 and Comparative Examples 1 to 7
[0174] A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the weight percentage and / or weight-average molecular weight of the binder resin as described in Table 1 below was varied during the manufacture of the anode.
[0176] 1st Binder Resin (Weight%) Second binder resin (weight%) Third binder resin (weight%) weight-average molecular weight First binder resin Second binder resin Example 1 37.5 12.5 50 750,000 500,000 Example 2 12.5 37.5 50 Example 3 25 25 50 Example 4 50 12.5 37.5 Example 5 37.5 50 12.5 Example 6 37.5 12.5 50 1,300,000 500,000 Example 7 37.5 12.5 50 100,000 500,000 Example 8 37.5 50 12.5 750,000 100,000 Comparative Example 1 100 0 0 750,000 500,000 Comparative Example 2 50 0 50 Comparative Example 3 0 100 0 Comparative Example 4 0 50 50 Comparative Example 5 0 20 80 Comparative Example 6 43 0 57 Comparative Example 7 75 25 0
[0177] Measurement of weight-average molecular weight
[0178] The weight-average molecular weight of the first binder resin and the second binder resin used in the above examples and comparative examples was measured under the following measuring device and conditions.
[0179] GPC measuring device: ACQUITY APC (Waters)
[0180] Column: PL gel Mixed-B + C (Agilent)
[0181] Column temperature: RT (20~25℃)
[0182] Eluent: DMF / 0.05M LiBr
[0183] Flow rate: 1.0 ml / min
[0184] Detector: Waters 2414 RI detector
[0185] Sample concentration: ~1 mg / ml (0.45 µm syringe filter)
[0186] Injection volume: 10 µl
[0187] Correction curve: Polystyrene
[0189] Performance evaluation
[0190] 1. Adhesion strength measurement method
[0191] After cutting the electrode, which has been dried at 50°C for 2 hours, into a size of 15 cm × 2 cm, attach it with the electrode surface to a slide glass with double-sided tape attached, and prepare three samples for a peel test through lamination.
[0192] The above peel test sample is loaded into a UTM capable of measuring adhesion strength, and a 90° peel test is performed to measure the peel resistance (gf / cm) and calculate the adhesion of each electrode.
[0193] <Analysis Conditions>
[0194] - Sample width: 20mm
[0195] - Propagation speed: 300 mm / min
[0196] - Valid data calculation range: 10mm ~ 40mm
[0198] 2. Output Density
[0199] When a 5Ah pouch cell was made using the batteries manufactured in the above examples and comparative examples, the maximum output per unit weight was measured.
[0200] The maximum output that can be discharged above the lower limit voltage for 10 seconds at the point where the battery output is minimum was determined, and the minimum output point of the lithium-sulfur battery used was the SOC (state of charge) 75 point. At this point, after applying a 5.0C 10sec discharge pulse, the cell resistance was converted to calculate the maximum output reaching the lower limit voltage of 1.5V, and this was divided by the battery weight to calculate the maximum output per weight (output density).
[0202] Adhesion (gf) Power density (kw / kg) Example 1 17.2 3.3 Example 2 8.3 2.9 Example 3 11.8 3.1 Example 4 13.2 3.19 Example 5 9.3 3.04 Example 6 15.2 3.22 Example 7 11.5 3.13 Example 8 9.3 3.09 Comparative Example 1 3.9 1.6 Comparative Example 2 2.8 1.54 Comparative Example 3 1.8 1.3 Comparative Example 4 - - Comparative Example 5 - - Comparative Example 6 2.3 1.4 Comparative Example 7 3.6 1.57
[0203] According to Tables 1 and 2 above, it can be confirmed that high adhesion strength and output density without sedimentation can be achieved only when all three types of binder resins are combined. Specifically, Examples 2 to 5 varied the content of at least one of the three binder resins, and Examples 6 to 8 varied the weight-average molecular weight of the first binder resin and the second binder resin.
[0204] In particular, from Comparative Examples 1 to 7, it can be confirmed that when no single binder resin among the three types of binder resins is included, the powder settles in the slurry and cannot secure any adhesive strength, or exhibits very low adhesive strength compared to the examples.
Claims
Claim 1 A binder composition for a lithium-sulfur battery electrode comprising a first binder resin, a second binder resin, and a third binder resin, wherein the first binder resin is lithium-substituted polyacrylic acid, the second binder resin is polyvinyl alcohol, and the third binder resin is a colloidal particle-type aqueous binder resin which is an acrylic polymer comprising repeating units derived from at least one monomer among acrylic monomers, and does not include a nonionic organic polymer containing one or more nitrogen atoms. Claim 2 A binder composition for a lithium-sulfur battery electrode according to claim 1, wherein the first binder resin comprises at least one lithium-substituted polyacrylic acid, and the weight-average molecular weight (MW) of the lithium-substituted polyacrylic acid is 300,000 to 1,500,000. Claim 3 In paragraph 2, the first binder resin is a binder composition for a lithium-sulfur battery electrode comprising at least two types of lithium-substituted polyacrylic acids with different molecular weights. Claim 4 A binder composition for a lithium-sulfur battery electrode according to claim 1, wherein the weight-average molecular weight (MW) of the second binder resin is 10,000 to 1,000,000. Claim 5 delete Claim 6 A binder composition for a lithium-sulfur battery electrode according to claim 1, further comprising a water-based binder resin as the fourth binder resin. Claim 7 A binder composition for a lithium-sulfur battery electrode according to claim 1, wherein, based on a total of 100 weight% of the electrode binder composition, the first binder resin comprises 10 to 80 weight%, the second binder resin comprises 1 to 50 weight%, and the third binder resin comprises 10 to 80 weight%. Claim 8 delete Claim 9 A positive electrode for a lithium-sulfur battery comprising a positive current collector and a positive active material layer formed on at least one surface of the positive current collector, wherein the positive active material layer comprises a positive active material and a binder resin, and the binder resin comprises a binder composition for a lithium-sulfur battery electrode described in any one of claims 1 to 4, 6, and 7. Claim 10 A lithium-sulfur battery comprising a positive electrode according to claim 9, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte.
Citation Information
Patent Citations
Aqueous composite binder, negative electrode slurry, preparation method of negative electrode slurry, negative electrode plate, lithium ion battery cell, lithium ion battery pack and application of lithium ion battery pack
CN112736247A
Binder for improving a adhesion of positive electrode, positive electrode for lithium secondary battery including the same and lithium secondary battery including the positive electrode
KR1020210015048A
